Analisis Faktor yang Berhubungan dengan Keikutsertaan Ibu dalam program Imunisasi di Posyandu Desa Patondon Salu - Mutiara Asysyam; Mardhatillah; Khaeriyah Adri (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2025)
Immunization is a health effort to protect individuals from preventable diseases such as diphtheria, tetanus, and measles. Approximately 19.4 million children worldwide have not received complete immunization, including in Indonesia. Based on data, the coverage of Complete Basic Immunization (CBI) in Enrekang Regency reached 81.81% in 2023. This study aims to analyze the factors related to mothers’ involvement in the immunization program. A quantitative research method with a cross-sectional design was employed and analyzed using the chi-square test. The study population consisted of all mothers of infants and toddlers in the Posyandu of Pattondon Salu Village, totaling 181, with 125 selected as samples through purposive sampling. The findings revealed a significant relationship between family support and health worker support with mothers’ participation in the immunization program (p-value < 0.05), while mothers’ knowledge did not show a significant association with participation in the program